Trellis-coded unitary space-time modulation. - Bahceci, I. (IEEE Transactions on wireless communications)
Space-time coding is well established for high data rate communications over wireless channels with perfect channel state information. On the other hand, the case where the channel state information is unknown has received limited attention. Recently, a new signaling scheme called unitary space-time modulation that is suitable for the latter case has been proposed. We describe the use and design of trellis-coded space-time modulation schemes that use unitary space-time constellations. We construct these codes using a novel suboptimal code design criteria and study the performance of trellis-coded unitary space-time modulation for block fading channels under the assumption of no channel state information. Simulation results show that the proposed schemes improve the performance compared to uncoded transmission with the same spectral efficiency. The results are also compared with the turbo-coded modulation scheme Bahceci (2002) and the differential detection scheme described Jafarkhani (2001) under the same assumptions.